Enablers and barriers to healthy eating among hospital nurses: A systematic review. (February 2023) - Marko, Sarah; Wylie, Stephanie; Utter, Jennifer
Abstract: Background: Nurses are the largest health professional body globally. Despite the significant role they play in healthcare, nurses exhibit poor dietary habits and have high rates of chronic diseases. Understanding the factors underlying healthy eating for nurses in the workplace is important to implement effective interventions. Objective: To identify enablers and barriers related to healthy eating among nurses employed in a hospital setting. Design: A systematic literature review of qualitative, quantitative, and mixed methods research (PROSPERO ID: CRD42021290913). Data sources: A comprehensive systematic search was conducted across PubMed, CINAHL, Embase, Web of Science and ProQuest databases for papers published after January 2015. Methods: Two authors independently screened titles and abstracts of 4139 deduplicated studies, performed critical appraisals on eligible studies using the Mixed Methods Appraisal Tool and extracted data relevant to the research question. This review includes papers that examined nurses' eating behaviours specifically, were conducted in a hospital setting and distinguished healthy eating from other behaviours. Data synthesis was conducted through descriptive summarisation of studies and enablers and barriers were classified according to the socio-ecological model. Results: A total of 29 studies were identified with 8024 participants. 8 studies were qualitative, 18 quantitative, and 3 were mixed method design. At an environmental level, barriers were high accessibility and availability of unhealthy foods, high cost and low availability of healthy foods and lack of storage and preparation facilities, while an enabler was close proximity to healthy options. Novel organisational enablers were considered roster planning which allowed for established routines around meals, and structured workplace programs that encouraged improvement in health behaviours, while barriers were shift work, inconsistent rosters and high work demands. An interpersonal enabler was supportive networks while barriers were work culture, social norms of celebrations and gifts of food from patients. Finally, intrapersonal barriers were stress and fatigue, personal values, beliefs, attitudes, and individual characteristics, with the latter two also acting as enablers. Conclusions: This review identifies the complexity and interconnectedness of enablers and barriers to healthy eating across four domains of the socio-ecological model. Multi-faceted strategies which address factors across several domains are recommended for healthcare organisations to facilitate healthy eating among nurses. Further research is needed to assess these strategies and understand the extent to which eating behaviours can be improved.